Age-Related Differences between Maximum Flight Height of Basic Skills on Floor, Beam and Vault and Physical Condition of Youth Female Artistic Gymnasts - Christoph Schärer; Luca Reinhart; Klaus Hübner (MDPI AG, 2023)
In women's artistic gymnastics, difficult elements with great flight heights have to be performed on the apparatuses. However, the importance of the physical condition for generating flight height and its development with age remains elusive. Therefore, we investigated the age-related differences of lower body power, reactive strength, 20 m sprint speed, flight heights (basic elements on beam and floor) and run-up speed on the vault of 33 youth female gymnasts. Further, we calculated correlations between all parameters separately for different age groups (7-9 y; 10-12 y; 13-15 y). We found larger differences between the age groups 7-9 y and 10-12 y than between 10-12 y and 13-15 y on the apparatuses (10-12 y vs. 7-9 y: +23% to +52%; 13-15 y vs. 10-12 y: +2% to +24%) and for physical conditioning variables (10-12 y vs. 7-9 y: +12 to +24%; 13-15 y vs. 10-12 y: + 5% to +16%). The correlations between flight heights and physical condition were the lowest for age group 7-9 y (r: from −0.47 to 0.78; 10-12 y: r: from −0.19 to 0.80; 13-15 y: r: from −0.20 to 0.90). An optimal application of the physical condition to enhance the gymnastics-specific performance (e.g., flight height) is strongly age-dependent. Regular monitoring of jumping abilities and the derivation of training recommendations can accelerate this development and the future performance of young athletes.